Vision Blinding of Participants in Limb Prosthetic Research Is Unnecessary. Issue 3 (July 2020) - Clark, Anna Marie; Fiedler, Goeran
Abstract : Introduction: This research addresses a common limitation in prosthetic and orthotic research, where subject blinding, for example, concealment of the group assignment, is difficult to implement. The purpose of this study was to investigate how effectively people with limb prostheses can be blinded to a typical research intervention. It was hypothesized that vision blinding reduces the accuracy of patients' assessment of prosthesis alignment changes. Methods: Users of a lower-limb prosthesis who were able to walk without aid were recruited as participants for this randomized crossover intervention study. Exclusion criteria were visual impairments and use of a prosthesis that disallows temporary alignment changes. Blinding (four levels) and prosthetic ankle alignment perturbation (five levels) were combined to result in a total of 20 randomized conditions per participant. Participants' accuracy and surety of assessing the alignment perturbation were evaluated as the main outcome measures. Results: Correctness of alignment assessment with and without blinding was not found to be significantly different ( P = 0.230). Subject's surety about their own assessments was significantly lower with vision blinding ( P = 0.005). Conclusions: Vision blinding did not seem to affect subjects' awareness of prosthetic interventions.